From Chastity Education to the Inclusion of Sexual Minorities? Textbooks on Ethics (dôtoku) and Hygiene (hoken) in Contemporary Japan - Kobayashi, Ami; Henninger, Aline (Historia y Memoria de la Educación, 2023)
UNESCO recommends that textbooks should be used to help students dismiss stereotypes. By containing stories that give prominence to multiple gender categories (men, women, transgender, for example) and various sexual orientations, such as lesbian, gay, and bisexual, textbooks can show the prejudicial effect of the division of humankind into two sexes and the imposition of heterosexuality. However, even today, schoolbooks in many countries provide very little space for this topic. Japan is not an exception. Since the emergence of the modern school system in the nineteenth century, sexual education, especially topics related to sexual minorities, has been absent from schoolbooks. Due to the international and national gay rights movement and several legal changes regarding sex reassignment surgery, the situation started to change in the late 1990s. In this article we overview the changes in curriculum guidelines relating to sexualities from 1958 to 2017 and critically analyse the latest school textbooks (issued after 2017) on hygiene (grade 4) and on ethics (grade 7-8). We discuss whether sex education in Japan, which was called “chastity education” (junketsu kyōiku) until 1972 and has previously been dominated by heteronormative values, has indeed transformed into “progressive” education that embraces sexual diversities. Referencing official documents of the Ministry of Education, we will argue that the Ministry of Education is medicalizing sex change surgery and labelling transgender children as “children with special needs”, while still imposing existing heteronormative gender norms on other non-minority children.